EFFECT OF 32 GRAM RESISTANT STARCH SNACK ON GLUCAGON LEVEL OF OBESE PATIENTS WITH DM TYPE 2 - Sadyah, Nur Anna Chalimah; Sinorita, Hemi; Ikhsan, M. Robikhul (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Glucagon plays a role in the pathophysiology of hyperglycemia in patients with type 2 Diabetes (DM). The characteristic of nutritional therapy for patients with type 2DM is using the resistant starch. This study was aimed to determine the influence of administration of 32 g snack made from resistant starch on glucagon level. METHODOLOGY This was a angle-arm before and after clinical trial design conducted among 21 obese patients with type 2DM attending endocrine clinic at RSUD Sarjito. The fasting glucagon levels were evaluated before and one hour after the administration of resistant starch. RESULTS Mean fasting glucose before and after snack with resistant starch were 203.18±132 and 201.64 pg/mL±33.84 pg/mL respectively. There was no significant difference in the fasting glucagon (p=0.170). Thirty-eight patients had a decrease in fasting glucose (11.92 pg/mL and 9.5 pg/mL respectively). The administration of resistant starch was very weakly correlated with the decrease in fasting glucagon (r=0.174) CONCLUSION There was no change in plasma glucagon level with administration of 32 gram snack made from resistant starch.